2021
DOI: 10.1590/0103-1104202113000
|View full text |Cite
|
Sign up to set email alerts
|

Fome, desemprego, corrupção e mortes evitáveis: faces da necropolítica

Abstract: EDITORIALEste é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições, desde que o trabalho original seja corretamente citado.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Our results showed that the working conditions of the CHWs in both state capitals and inland municipalities were unsatisfactory during the health emergency. In the same period, the public health care sector was marred by administrative difficulties and protracted political conflicts, with potentially serious repercussions on morbidity and mortality rates 7 , 23 , 53 . The health work process has been greatly compromised, the responses to the challenges imposed by covid-19 have been heterogeneous, which has had repercussions on the quality of life of health professionals 54 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the working conditions of the CHWs in both state capitals and inland municipalities were unsatisfactory during the health emergency. In the same period, the public health care sector was marred by administrative difficulties and protracted political conflicts, with potentially serious repercussions on morbidity and mortality rates 7 , 23 , 53 . The health work process has been greatly compromised, the responses to the challenges imposed by covid-19 have been heterogeneous, which has had repercussions on the quality of life of health professionals 54 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Apesar dos achados sugestivos de um efeito protetor das vacinas, é preciso considerar que mesmo com a alta porcentagem de idosos imunizados, o atraso no início da vacinação e a lentidão da campanha, pode ter culminado em uma baixa cobertura da população total, evidenciada, em especial, entre as faixas etárias mais jovens (COSTA et al, 2021). Por tratar de uma doença infectocontagiosa, é esperado um impacto nos casos e óbitos por COVID-19 mesmo em pessoas vacinadas, como no grupo analisado ao longo do trabalho.…”
Section: Saúde E Ambienteunclassified